Strategi Peritel Lokal Daerah Pasca Masuknya Peritel Lokal Nasional dan Peritel Asing - Khusniyah Purwani (Jurnal Aplikasi Bisnis, 2017)
This article describes the conditions of local retailers after the penetration of national retailers and foreign retailers. A local retailers is one of emergence originates from a local area. The form of their enterprise changes from the former conventional or traditional shops into local retailers which are managed according to modem standard with its